Evaluation Research in the Field of Reliability Science - Kundan Mishra, Viresh Sharma (Mathematical Statistician and Engineering Applications, 2023)
This article discusses the application of reliability in a variety of fields, including the scientific community. Given the significance of science in our everyday lives, it examines how the concept of reliability can shed light on the scientific method. There are many different technologies out there, and each of these technologies is important in its own right. One of these technologies is reliability.